Overexpression of the gibberellin 20-oxidase gene from Torenia fournieri resulted in modified trichome formation and terpenoid metabolities of Artemisia annua - Phithak Inthima (2018)
© 2017, Springer Science+Business Media Dordrecht. Gibberellins (GAs) are diterpenoid hormones, control various physiological developments in plants. The role of gibberellins on morphology and secondary metabolite production was examined in Artemisia annua, a medicinal plant that has been acknowledged as a source of artemisinin, an antimalarial compound. Subsequently, the GA20ox gene from Torenia fournieri (TfGA20ox2) was transferred to A. annua by Agrobacterium-mediated transformation. Compared with wild type plants, all nine transgenic plants showed significantly higher plant heights and artemisinin contents. The highest artemisinin content and yield in TfGA20ox2-overexpressing plants was around two-fold higher than wild type. Moreover, transgenic plants had higher numbers of branches (52.4%) and greater branch lengths (60–203%), but smaller leaf size (77.6%). Interestingly, relative to wild type the number and size of glandular trichomes in transgenic leaves was about 30 and 35% higher, respectively. From GC–MS analysis, the proportion of diterpenes in transgenic plant extracts was 1.5-fold lower than those noticed in wild type, while the proportion of sesquiterpenes was increased about 1.6 times when compared to wild type. However, the content proportion of monoterpenes showed a slightly increase, whereas the level of triterpenes showed no variation. In addition, two monoterpenes (eucalyptol and borneol), four sesquiterpenes (α-caryophyllene, β-guaiene, δ-cadinene and β-cubebene) and one triterpenes (isomultiflorenone) were detected only in transgenic extract, whereas d-α-tocopherol, a diterpenoid compound was found only in wild type but not transgenic plant. These results suggested that gibberellins play a significant role in regards to morphology, trichome formation and terpenoid metabolite production in A. annua.